PROTEAN CAREER SEBAGAI PARADIGMA BARU EFEKTIVITAS BOUNDARYLESS CAREER - -, Kartinah - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2005)
Abstract In this 21st century, developments have strongly influenced stakeholders as a form of a new paradigm of transformation. Globalization and the development of information technology pushed the organization to change its structure and other managerial aspects. By having human resources that have flexibility and ability to easily adapt into a dynamic environment would be major key in creating a faster, more efficient organization. The changes of organizational structure formed into new paradigm that is career development is driven by the individual itself. The outlook of career from traditional comer into boundaryless career. It indicates that protean career has been born. Protean career becomes a new challenge in managing human resources in developing individual career in order to make organization sustainable into competitive advantage. Keywords: Tranformation, protean career, metaskills, management career, boundaryless career.